2010
DOI: 10.1627/jpi.53.184
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Wet Oxidation of Phenol Using Regeneration of Pt/Al<sub>2</sub>O<sub>3</sub>

Abstract: Removal of phenol by wet air oxidation was conducted with 1 wt% Pt/Al2O3 catalyst in a batch reactor and in a continuous flow fluidized bed reactor with air lift tube operated at 423 K and 1.4 MPa. After 60 min in the batch reactor with initial phenol concentration of 1000 mg/l, almost complete conversion into CO2 and H2O was achieved. Pt/Al2O3 catalyst deactivation was observed during the wet oxidation reaction. TEM, EDX, XPS and TPO analyses showed the deactivation was caused by formation and deposition of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Pre-sonication of the sludge to disintegrate the flocs and improve solubility was found to be inefficient. Lee et al [12] carried out CWAO of phenol with 1 wt% Pt/ Al 2 O 3 in a batch reactor and in a continuous-flow fluidized bed reactor with an air lift tube operated at 423 K and 1.4 MPa. They reported that almost complete degradation of phenol into CO 2 and water was achieved in the batch reactor after 1 h for an initial phenol concentration of 1 g/l.…”
Section: Introductionmentioning
confidence: 99%
“…Pre-sonication of the sludge to disintegrate the flocs and improve solubility was found to be inefficient. Lee et al [12] carried out CWAO of phenol with 1 wt% Pt/ Al 2 O 3 in a batch reactor and in a continuous-flow fluidized bed reactor with an air lift tube operated at 423 K and 1.4 MPa. They reported that almost complete degradation of phenol into CO 2 and water was achieved in the batch reactor after 1 h for an initial phenol concentration of 1 g/l.…”
Section: Introductionmentioning
confidence: 99%